Analysis of the Application of Freudian Theory in the Pattern of Fascist Propaganda in Indonesia - Agustina, Dini; Widaningsih, Titi; Marta, Rustono Farady (Jurnal Indonesia Sosial Sains, 2024)
Propaganda is a powerful tool for shaping public perception, especially in the context of fascism. This study analyzes the application of Freudian theory to fascist propaganda in Indonesia, particularly during the New Order era under Soeharto’s regime. Fascism in Indonesia began in 1933 with the rise of organizations like the Nederlandsche Indische Fascisten Organisatie (NIFO) and the Indonesian Fascist Party (PFI). During the New Order, propaganda was used to manipulate public opinion, suppress opposition, and maintain power. This research employs a qualitative literature review method, analyzing historical records, media sources, and academic writings. The study specifically examines how Freudian concepts, such as unconscious fears and mass psychology, were used to influence public perceptions, particularly in relation to the G30S/PKI case. The findings reveal that the regime exploited public fears of communism, using propaganda to justify repression and control. This research highlights the importance of understanding the psychological underpinnings of propaganda and suggests that further studies could explore the broader implications of these techniques in different political contexts.